I see no equal signs
What are we verifying ?
Hi. Can you verify the following:
(cosθ) / (sinθ – 1) + (cosθ)/ (1 + sinθ)
(1 / cos^2θ) – (2) (1/cos^2θ) (sinθ / cosθ) + (sin^2θ / cos^2θ)
2 answers
Oooops. Its this one. Sorry.
(cosθ) / (sinθ – 1) + (cosθ)/ (1 + sinθ) = -2tanθ
(1 / cos^2θ) – (2) (1/cos^2θ) (sinθ / cosθ) + (sin^2θ / cos^2θ) = (1 - sinθ) / (1 + sinθ)
(cosθ) / (sinθ – 1) + (cosθ)/ (1 + sinθ) = -2tanθ
(1 / cos^2θ) – (2) (1/cos^2θ) (sinθ / cosθ) + (sin^2θ / cos^2θ) = (1 - sinθ) / (1 + sinθ)